(untitled) (LEARNing Landscapes, 2008)
The following article demonstrates the use of the dramatic scenario, The Insurrection (a TAR/ethno-drama fiction work) to teach fundamental educational administration concepts to graduate and preservice teacher candidates. The scenario was written specifically to address the conflicts related to communication within a secondary school community and is used as a provocation tool in classroom discussions.